Development of Recording and Reporting of Nosocomial Infection Surveillance System in Surabaya Premier Hospital - Miftakhul Janah; Santi Martini; Hari Basuki Notobroto (Health Notions, 2017)
Nosocomial infection is infection that occurs in patients who are hospitalized. One of infection control programs is the surveillance activity. Refer to the Instructions Practical Hospital nosocomial infections Surveillance by the Health Ministry (2011), computer usage in surveillance activities will increase the efficiency of data collection and analysis. The aim of this study was to develop recording and reporting nosocomial infection surveillance system. This study type was action research with System Development Life Cycle (SDLC) method where in the stages of SDLC were planning, analysis, design, implementation and usage. The instruments used in this study were by creating DFD, ERD, data dictionary then continued with the development of applications using PHP and MySQL. Data collection was committed through interviews and observations. The results of this research was web-based applications tested using the method of Technology Acceptance Model (TAM). Keywords: Nosocomial infection surveillance, Recording and reporting, System development